Cryptic diversity on the genus Caenolestes (Caenolestidae: Paucituberculata) in the Ecuadorian Andes - Carrión-Olmedo, Julio C.; Brito, Jorge (PeerJ, 2025)
The shrew-opposums of the genus Caenolestes (Thomas, 1895) belong to a group of Ameridelphian marsupial mammals in the order Paucituberculata, an order in which most of its representatives are extinct. This genus contains five formally described species: C. caniventer, C. convelatus, C. condorensis, C. fuliginosus, and C. sangay, all with type localities in Ecuador, plus at least three candidate species from Colombia now recognized as subspecies C. convelatus barbarensis, C. fuliginosus centralis and C. fuliginosus obscurus. Records of this genus are not abundant, both in biological collections and in sequence repositories (GenBank); thus, showing a discontinuous geographical distribution that could be a consequence of incomplete sampling. Systematic expeditions by the Instituto Nacional de Biodiversidad (INABIO) have increased the geographic sampling of this genus in Ecuador, which allowed us to reevaluate its genetic diversity. We obtained 43 sequences of cytb and 30 of RAG1 from 28 Ecuadorian localities in 12 Provinces, including novel topotypical material from C. caniventer, C. convelatus, and C. condorensis. We present a new hypothesis on the genetic diversity of Caenolestes using maximum likelihood inference for phylogenetic analysis, estimate p-genetic distances and divergence times for the genus. We found a species complex in the C. fuliginosus clade, with at least three candidate new species, having a threshold above 5% for the estimated genetic distance of the cytb among them. Also, we found two additional lineages hidden within C. caniventer. We expect that future work, with similar or larger sampling efforts in Colombia and Peru would reveal greater phylogenetic diversity and more complete evolutionary relationships.
Keywords: Marsupials; Species complex; Andean biodiversity; Molecular phylogenetics